PENINGKATAN KETERAMPILAN CREW KAPAL DALAM PENANGANAN MUATAN GUNA MENCEGAH KERUSAKAN MUATAN DI KAPAL MT. BAHARI SATU - Rahmat Maulana (Politeknik Ilmu Pelayaran Semarang, 2019)
ABSTRACTShip cargo is an object of transportation in the sea transportation system, by transporting the cargo ofa commercial shipping company that can obtain revenue in the form of mining money which is verydecisive in the survival of the company and financing port activities. The several events on board thatoccurred such as load damage caused by the lack of skills of the crew in handling cargo.The methodused in this study is a qualitative method that produces descriptive data in the form of written wordsfrom people and observed behavior. The subject process and meaning are more highlighted inqualitative research. The data collection techniques used such as observation and documentation.Ship cargo (cargo) is an object of transportation in the sea transportation system, by transporting thecargo of a commercial shipping company. Therefore, handling cargo on board is very important toget profit for the company. To support cargo security, human resources are experts in their fields,namely those who have skills in handling cargo. Without handling the load by the cargo crew can bedamaged, and can cause losses to the company. From the above problems we can discuss how toimprove the skills of the ship's crew in handling cargo